How to ‘future proof’ benefit-sharing from the use of DSI in agricultural research and development - Rouard, Mathieu; Sackville-Hamilton, Nigel; Reyes, Paula; Sansolini, Carolina; Pinilla Meza, Gustavo Andres; Halewood, Michael; Toledo, Álvaro (2024)
CGIAR Genebank Side event: 2nd meeting of the Ad Hoc Open-ended Working Group on Benefit-sharing from the Use of Digital Sequence Information on Genetic Resources 13 August 2024